Evaluating 5S Cultural Program for Character Education: A CIPP Model Study in Indonesian Elementary School - Putri, Dissya Apita Aryana; Sanoto, Herry (Papanda Publisher, 2025)
The rapid advancement of digital technology has led to a decline in student character, particularly in politeness, empathy, and respectful social behavior. In response, SD Negeri Gendongan 01 Salatiga implemented the 5S cultural program (Smile, Greet, Salute, Polite, Courteous) as a strategy for character education. This study aims to evaluate the implementation of the 5S program using the CIPP evaluation model (Context, Input, Process, Product) aligned with school management functions. This qualitative evaluative research employed the CIPP model and involved 21 purposively selected participants, including the principal, six teachers, two staff members, and twelve students. Data were gathered through structured interviews, observations, and documentation. The analysis followed Miles and Huberman's qualitative technique, ensuring triangulation for validity. The context evaluation revealed that the 5S program aligns well with the school’s vision and mission, emphasizing the development of character traits. Input evaluation showed strong stakeholder involvement, though limited funding and infrastructure constrained implementation. Process evaluation indicated inconsistency in teacher role modeling and selective student engagement. Product evaluation showed positive behavioral changes in students, but the outcomes were inconsistent and not yet optimal. The findings highlight the crucial role of consistent teacher behavior in influencing student participation and program effectiveness. The integration of the CIPP model with school management phases provides a comprehensive framework for evaluating non-academic programs. This research contributes theoretically to character education implementation and offers practical recommendations for strengthening school-based cultural programs.